High optical correction system based 800x600 analog spatial light modulator - Bida, Falah A.; Salman, Muayad Hanoon; Naser, Hayder A. (Iraqi Journal of Science, 2022)
In this work, a modern optical system based on modulation technique is constructed to achieve the retrieval of optical defects and distortions of the images behind dark barriers.  A 800x600 analog spatial light modulator (SLM) is used in this technique with a 632.8nm He-Ne laser, a circular metallic mesh (CMM) is imaged and disturbed and then dealing with our system. The SLM was confirmed for irregularity improvement such as variable diffracted optical element (DOE) control. The obtained results showed that the effect of distortion has been treated and reduced to be minimum by controlling phase and amplitude modulation of the scattered wave front utilizing the SLM. The obtained images showed identical to the original image with limitation in the intensity distribution due to the pixelated structure of SLM. This technique represents the most appropriate solution to the problem of dispersion in images with the lowest costs and best results. The most important applications of this technology are the ability of providing high-resolution imaging where viewing through a deviant medium is inevitable.